An Improved NLC and Capacitor Voltage Control Method for Medium-/Low-Voltage MMCs - ZHANG Wei, HAN Junfei, ZHONG Ming, WANG Yuqiang (Shanghai Jiaotong Daxue xuebao, 2023)
The modular multilevel converter (MMC) suffers from low output level and high harmonic distortion in medium-/low-voltage applications such as direct current (DC) distribution networks. In addition, the capacitor voltage of MMC is coupled with DC bus voltage in the traditional modulation method, leading to large fluctuations of capacitor voltages and deviation from the rated value under DC bus voltage margin. In order to solve the problems above, this paper proposes an improved nearest level control method, which can increase the output level of medium-/low-voltage MMCs by introducing a step wave correction. Based on the proposed modulation method, a capacitor voltage feedback control is thus proposed to limit the range of capacitor voltage fluctuations and improve equipment safety. The effectiveness of the proposed method is verified by MATLAB/Simulink simulation and real-time digital simulation system hardware-in-the-loop test.